CM 2022
DOI: 10.18137/cardiometry.2022.21.4149
|View full text |Cite
|
Sign up to set email alerts
|

Development of an experimental model of tumor growth under hypothyroidism

Abstract: Aim. Our aim has been to develop an experimental model of the tumor growth against the background of hypothyroidism in rats of both genders in order to study possible influence made by hypothyroidism on progression of malignant tumors of various histological types. Materials and methods. In our studies we have used 100 outbred albino rats of both genders, with an individual body mass of 150-180 g. The female rats (n=30) and the male rats (n=30) have received Mercazolil at a day dosage of 2,5 mg/100g of the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Previously, we found that induced hypothyroidism inhibited the growth of transplanted Guerin's carcinoma and increased life expectancy only in female rats, while in male rats, despite the fact that the size of the tumors was smaller at the initial stages, after 2 weeks of the experiment it was comparable with the parameters in the animals with the independent tumor growth, and no increase in life expectancy was observed [16,17]. An analysis of the content of hypothalamic Gn-releasing and pituitary tropic hormones LH, FSH and prolactin (PRL) in rats of both sexes is presented in Table 1 herein.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Previously, we found that induced hypothyroidism inhibited the growth of transplanted Guerin's carcinoma and increased life expectancy only in female rats, while in male rats, despite the fact that the size of the tumors was smaller at the initial stages, after 2 weeks of the experiment it was comparable with the parameters in the animals with the independent tumor growth, and no increase in life expectancy was observed [16,17]. An analysis of the content of hypothalamic Gn-releasing and pituitary tropic hormones LH, FSH and prolactin (PRL) in rats of both sexes is presented in Table 1 herein.…”
Section: Resultsmentioning
confidence: 71%
“…Since the HPT axis is associated with the reproductive system, and since we previously established the sex specificity of the effect of hypothyroidism on the growth of Guerin's carcinoma [16], it is of particular interest to study changes in the functioning of the HPG axis in animals of both sexes with Guerin's carcinoma growing against the background of a simulated thyroid hormone deficiency…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that in female rats, hypothyroidism slowed down the increase in the volume of primary tumors of Guerin's carcinoma and prolonged their life expectancy. In males, a slight slowdown in the tumor growth was noted only up to day 14 after inoculation, then the tumor grew rapidly, and its volume did not differ from that recorded in the reference group, and no increase in life expectancy was reported [9,10]. It was just during that period, upon expiration of 19 days of the tumor growth, when significant gender differences in the growth of Guerin's carcinoma were revealed by us, and studies of indicators in blood and tissues were carried out.…”
Section: Resultsmentioning
confidence: 76%
“…Previously, we have shown that the growth of Guerin's carcinoma against the background of hypothyroidism in the females slows down that makes its impact on a prolongation in life spans, while inhibition of the tumor growth was revealed in the males only at the initial stages after the tumor cell transplantation, then the tumor progressed rapidly, and, as a result, the life spans did not differ from the respective indicators in the group with the normal state of the thyroid gland [10].…”
Section: Methodsmentioning
confidence: 80%
“…It is known that the growth of a malignant tumor has a significant and often sex-dependent effect on the body's regulatory axes [9]. Moreover we previously found that induced hypothyroidism had an inhibitory effect on the growth of Guerin's carcinoma and S45 sarcoma only in the females, but not in the males [10,11].…”
Section: Introductionmentioning
confidence: 78%